Valorization of Technical Lignin for the Production of Desirable Resins with High Substitution Rate and Controllable Viscosity. Issue 17 (31st March 2020) - Pang, Bo; Lam, Su Shiung; Shen, Xiao‐Jun; Cao, Xue‐Fei; Liu, Shi‐Jie; Yuan, Tong‐Qi; Sun, Run‐Cang
Abstract: The valorization of lignin to replace phenol is significant in the production of phenolic resins. However, a great challenge is to produce lignin‐based resin (LR) with a suitable viscosity and high substitution rate of lignin to phenol. In this study, LRs were produced using hardwood technical lignin derived from the pulping industry. Structural analysis of the LRs indicated that the unsubstituted para and ortho carbon atoms of the aromatic ring influenced the curing temperature and activation energy of the resins. The curing kinetics and thermal decomposition study implied that urea and methylene groups in cured LRs were significant factors that affected the thermal stability negatively. The prepared LRs showed desirable features if used as adhesives to make plywood. This is the first approach in which a substitution rate of up to 65 % is achieved for low‐reactive‐site hardwood lignin, which provides a solution to the challenge of the simultaneous realization of the high addition of lignin and the adaptive viscosity of resins. Abstract : Ready resins : Lignin‐based resins are produced using hardwood technical lignin derived from the pulping industry. This is the first approach in which a substitution rate of up to 65 % is achieved for low‐reactive‐site hardwood lignin. This provides a solution to the challenge of the simultaneous realization of the high addition of lignin and the adaptive viscosity of resins.